The genome sequence of the eastern grey squirrel, Sciurus carolinensis Gmelin, 1788 - Mead, Dan (Wellcome Open Res, 2020)
We present a genome assembly from an individual male Sciurus carolinensis (the eastern grey squirrel; Vertebrata; Mammalia; Eutheria; Rodentia; Sciuridae). The genome sequence is 2.82 gigabases in span. The majority of the assembly (92.3%) is scaffolded into 21 chromosomal-level scaffolds, with both X and Y sex chromosomes assembled.